2012
DOI: 10.1111/j.1467-7652.2012.00688.x
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of Arabidopsis and Rice stress genes’ inducible transcription factor confers drought and salinity tolerance to rice

Abstract: SummaryRice yield is greatly affected by environmental stresses such as drought and salinity. In response to the challenge of producing rice plants tolerant to these stresses, we introduced cDNA encoding the transcription factors DREB1A and DREB1B under the control of the stress inducible rd29 promoter. Two different indica rice cultivars were used, BR29, an improved commercially cultivated variety from Bangladesh and IR68899B, an IRRI bred maintainer line for hybrid rice. Agrobacterium mediated transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 27 publications
8
66
1
Order By: Relevance
“…Heterologous expression of alien genes has been a practical an effective approach for engineering improvements into crop plants (Pratap and Kumar 2014). Usually plant genes that confer an important function are employed to improve the same agricultural character in related crop plants (Datta et al 2012;Jacobs et al 2011;Li et al 2012;Oliva et al 2014;Pasquali et al 2008;Shin et al 2006;Zhao et al 2015;Zheng et al 2015). Unfortunately, It is inefficient to improve rice by transforming one gene at a time, but high-throughput overexpression of cDNA libraries from other plants can surpass this limitation, because foreknowledge of gene function is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous expression of alien genes has been a practical an effective approach for engineering improvements into crop plants (Pratap and Kumar 2014). Usually plant genes that confer an important function are employed to improve the same agricultural character in related crop plants (Datta et al 2012;Jacobs et al 2011;Li et al 2012;Oliva et al 2014;Pasquali et al 2008;Shin et al 2006;Zhao et al 2015;Zheng et al 2015). Unfortunately, It is inefficient to improve rice by transforming one gene at a time, but high-throughput overexpression of cDNA libraries from other plants can surpass this limitation, because foreknowledge of gene function is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…This promoter was identified in Arabidopsis and shown to have a basal expression, which is significantly increased under high salt and other stress conditions [35,41]. There are many reports that the stress-regulation of rd29A is not only found in its native host Arabidopsis but also in crop plants such as potato (own results, [34,42]), rice [43], mulberry [44], soybean [45], and peanut [46]. The relatively stable GG accumulation in transgenic potatoes of the series Alba-rd29A-AF indicated that changes in the relative expression of ggpPS and genes for competing enzymes such as sps might be at least partly responsible for the developmental change in GG accumulation in plants expressing ggpPS by CaMV 35S promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Over expression of stress-responsive rice SNAC genes such as SNAC1, OsNAC6/SNAC2 and OsNAC5 improves drought tolerance. Significant level of improvement for drought tolerance in rice was observed when there was an over-expression of TFs like AREB1 [85] and DREB/CBF [85][86][87].…”
Section: Drought Tolerancementioning
confidence: 99%